O processo eletrônico e a evolução disruptiva do direito processual civil - Pegoraro Junior, Paulo Roberto (2018)
The implementation of the electronic lawsuit in Brazil derived from the gradual assimilation of data processing tools by the Judicial Power, which led to the initiative of several courts to develop an operationally functional system, and culminated in putting the Electronic Lawsuit Act into effect. The adoption of the electronic lawsuit model, despite representing a significant reinforcement of the fundamental right to have a lawsuit finished in a reasonable time, thus contributing to its celerity, has been more than a simple tool: it is a significant element of the disruptive evolution of the Civil Procedural Law. The implications of such assimilation includes, among other factors: overcoming the territorial jurisdiction in the face of the deterritorialization phenomenon, due to the ubiquity of the electronic lawsuit system; understanding of a hypertext model which translates into a dynamic way of presenting both the parties’ arguments and the content of the decision; possibility of omnidirectional contradictory statement by means of groupware, in an effective community of procedural work; possibility of automated decision-making; and even the appropriation of elements of artificial intelligence for managing juridical information and decisions. Therefore, this thesis focuses on the way through which the electronic lawsuit may be the cause (and also a consequence) of the disruptive evolution of the Civil Procedural Law, without disregarding the criticisms of the model, but rather considering that the environment in which the lawsuit takes place is not neutral, as it both affects and often conditions the message content.